A Field Calibration Method for UHF Partial Discharge On-line Monitoring System Based on Cross-check Algorithm - Nan LI; Songyuan LI; Xuejun SHANG; Bowen GUO; Lin LI; Guoqiang ZU; Kai HOU (Zhongguo dianli)
Partial discharge (PD) on-line monitoring device plays an important role in comprehensive perception and intelligent diagnosis of equipment conditions. Affected by the operational environment, manufacturing technology and other factors, the on-line PD sensors are deteriorated in performance with the increase of their service time, the sensors’ calibration is thus imperative. An optimized field calibration method is proposed for the internal ultrahigh frequency partial discharge (UHF-PD) sensors of on-line PD monitoring system. Firstly, the influencing factors on the field calibration of the UHF-PD on-line monitoring system are analyzed from three aspects including sensors’ working features, installation location and signal transmission attenuation properties. Then, a novel cross-check method is proposed based on the traditional GIGRE method. Through horizontal comparison between different phases and mirror comparison between input/output signals, the effects of absolute-value check on the accuracy of sensor’s calibration is significantly decreased, thus improving the overall calibration efficiency. Finally, the proposed method was applied in a 500 kV substation for field calibration of the UHF-PD on-line monitoring system, and identified three typical defects, including the degraded sensors’ sensitivity, unreasonable sensors arrangement and faulted acquisition board. The results verified the effectiveness and feasibility of the proposed method.